2011
DOI: 10.1038/mp.2011.113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for BDNF- and GABA-related dysfunctions in the amygdala of female subjects with major depression

Abstract: Women are twice as likely as men to develop major depressive disorder (MDD) and are more prone to recurring episodes. Hence, we tested the hypothesis that the illness may associate with robust molecular changes in female subjects, and investigated large-scale gene expression in the postmortem brain of MDD subjects paired with matched controls (n=21 pairs). We focused on the lateral/basolateral/basomedian (LBNC) complex of the amygdala as a neural hub of mood regulation affected in MDD. Among the most robust fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
297
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(329 citation statements)
references
References 76 publications
18
297
1
1
Order By: Relevance
“…Mice engineered to disrupt BDNF signaling display several phenotypes, including hyperphagia-induced obesity, enhanced aggression, changes in cognitive behavior, and blunted response to antidepressant treatments (Autry et al, 2011;Chan et al, 2006;Ito et al, 2011;Lyons et al, 1999;Monteggia et al, 2004;Monteggia et al, 2007;Sakata et al, 2013). In line with BDNF's ability to influence multiple pathways, markers of 5-HT signaling as well as GABAergic transmission are altered in these models (Deltheil et al, 2008;Guilloux et al, 2012;Homberg et al, 2014;Hong et al, 2008;Huang et al, 1999;Luellen et al, 2007;Martinowich and Lu, 2008;Rios et al, 2006;Sakata et al, 2009;Tripp et al, 2012). Consistent with data from manipulation of Bdnf in rodents, BDNF disruption in humans is associated with psychiatric manifestations and neurobehavioral alterations, including obesity and enhanced aggression (Ernst et al, 2012;Han et al, 2008).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Mice engineered to disrupt BDNF signaling display several phenotypes, including hyperphagia-induced obesity, enhanced aggression, changes in cognitive behavior, and blunted response to antidepressant treatments (Autry et al, 2011;Chan et al, 2006;Ito et al, 2011;Lyons et al, 1999;Monteggia et al, 2004;Monteggia et al, 2007;Sakata et al, 2013). In line with BDNF's ability to influence multiple pathways, markers of 5-HT signaling as well as GABAergic transmission are altered in these models (Deltheil et al, 2008;Guilloux et al, 2012;Homberg et al, 2014;Hong et al, 2008;Huang et al, 1999;Luellen et al, 2007;Martinowich and Lu, 2008;Rios et al, 2006;Sakata et al, 2009;Tripp et al, 2012). Consistent with data from manipulation of Bdnf in rodents, BDNF disruption in humans is associated with psychiatric manifestations and neurobehavioral alterations, including obesity and enhanced aggression (Ernst et al, 2012;Han et al, 2008).…”
Section: Introductionmentioning
confidence: 83%
“…Divergent 5-HT and GABA Gene Expression Changes Following BDNF Loss from Promoters I and II vs IV and VI BDNF deficiencies are strongly associated with misregulation of both 5-HT and GABA signaling pathways (Deltheil et al, 2008;Guilloux et al, 2012;Hong et al, 2008;Lyons et al, 1999;Rios et al, 2006;Sakata et al, 2009;Tripp et al, 2012). The 5-HT neurochemical signaling system has been consistently associated with control of aggressive behavior (Takahashi et al, 2011).…”
Section: Bdnf Produced From Promoters I and Ii Regulates Aggressionmentioning
confidence: 99%
“…76 For instance, using human postmortem samples and genetic studies in mice, we recently showed that BDNF levels are reduced in the amygdala of women affected with major depression, and that this reduction correlated with (and likely induced, based on mouse genetic studies) molecular adaptations in specific subsets of GABA-containing inhibitory neurons that target the dendrites of pyramidal neurons, a cellular compartment critical for integrating incoming information-rich signals. 77 We have speculated that a state of BDNF-dependent reduced dendritic inhibition may represent a novel stable state over time, although it is maladaptive in that it may mediate increased amygdala reactivity, a neural network endophenotype frequently observed in MDD and thought to underlie the rumination or bias for negative emotions in depressed subjects. 78 Supporting our age-by-disease interaction model, BDNF is also robustly downregulated with increasing age, suggesting that similar downstream changes may occur in older subjects (See Douillard-Guilloux et al 71 in this issue).…”
Section: Altered Biological Landscape and Physiological Homeostasis Imentioning
confidence: 99%
“…Research on the possible molecular pathways of depression demonstrated that the increased cell dysfunction in cortical and limbic areas of the brain can be observed in individuals suffering from depression [3,4] and is strongly related to the decrease in neurotrophic activity [5]. Therefore, the investigation of biomarkers, such as brainderived neurotrophic factor (BDNF), has attracted great interest, in order to clarify its role in the pathophysiology of depression [6].…”
Section: Introductionmentioning
confidence: 99%
“…BDNF is a protein expressed mainly in the central nervous system (CNS), and it has an important role in the survival and maintenance of neuronal function [7]. In fact, a low neurotrophic activity is associated with reduced numbers of cells in the prefrontal cortex [8], amygdala [9,10] and a decrease in hippocampal volume [11,12], indicating that the growth nerve factors, and more specifically, the changes in BDNF may play an important role in the development of depression [3,4,[13][14][15]. Furthermore, the dysfunction of the hypothalamuspituitary-adrenal (HPA) axis has been the most valid neurobiological theory to explain the pathophysiology of depression.…”
Section: Introductionmentioning
confidence: 99%